Severe influenza/respiratory syncytial virus infections and hospital antimicrobial stewardship opportunities: impact of a 4-year surveillance including molecular diagnosis. (22nd October 2020) - Bourgeois, Marc; Ausselet, Nathalie; Gerard, Veronique; de Canniere, Louis; Scius, Nathan; Michaux, Isabelle; Huang, Te-Din; Bogaerts, Pierre; Vandamme, Charlotte; Bihin, Benoît; Delaere, Benedicte
Abstract: Objective: To assess the prevalence of influenza and respiratory syncytial virus (RSV) in adults hospitalized for a respiratory infection in the winter months and to evaluate the impact of a viral diagnosis on empirical antimicrobial management (antibiotics and antivirals). Design: Observational cohort study. Setting: Acute-care university hospital. Patients: The study included 963 adult patients hospitalized over a 4-year surveillance period. Methods: Annual surveillance timelines were defined according to epidemiological criteria related to the circulation of RSV and influenza viruses in the general population. Patients were screened following a severe acute respiratory infection (SARI) case definition at the emergency department and were enrolled for molecular assay targeting influenza/RSV viruses after oral informed consent. Epidemiological and clinical data were recorded prospectively, microbiological investigations, antimicrobial management, and outcome data were reviewed retrospectively. Results: An influenza or RSV virus was documented in 316 of 963 patients (33%). Optimization of antimicrobial management (AM) was achieved in 162 of 265 patients (61%) with a positive viral diagnosis and no bacterial infection at admission (AM treatment not initiated, n = 111; discontinued, n = 51). In contrast, only 128 of 462 patients (28%) with negative microbiological investigations did not have AM treatment initiated (n = 116) or had such treatment discontinued (n = 12). Early, targeted antiviral treatment was prescribed in 235 of 253 patients (93%) confirmed with influenza. Epidemiological, clinical, and outcome data were similar in both groups. Conclusion: Epidemiological surveillance associated with influenza/RSV molecular diagnosis in adults hospitalized for severe winter respiratory infections dramatically enhanced antimicrobial management.